Small gastric hyperplastic polyp with acute bleeding as an unusual presentation of malignancy: A case report. Issue 22 (June 2018) - Park, Kyoung Sun; Lee, Seung-Woo; Lee, Junguee; Kim, Moon Sung; Park, Pyung Hwa; Moon, Sung Jin; Kang, Sang-Bum; Lee, Dong Soo
Abstract: Rationale: Gastric hyperplastic polyps are frequently found on upper gastrointestinal endoscopy and usually asymptomatic. Patients concerns: A 65-year-old man visited the emergency department due to melena. Emergency upper endoscopy revealed a semi-pedunculated polyp measuring 1.2 cm in diameter with blood oozing. We resected the polyp using snare polypectomy. Ulceration was noted on the polypectomy specimen and was thought to be a bleeding focus. Diagnoses: Histopathologic findings revealed hyperplastic polyp with focal well-differentiated adenocarcinoma in the ulcerated area and involvement of the lateral resection margin by carcinoma. Intervention: We performed additional endoscopic resection using endoscopic submucosal dissection at the previous polypectomy site. Outcome: At 1 year follow up, no recurrence or other distant metastasis was detected. Lessons: This is a rare case of upper gastrointestinal bleeding from a small gastric hyperplastic polyp, which was found to be adenocarcinoma. When bleeding small gastric polyps are encountered during endoscopy, the possibility of malignancy and wider resection should be considered.